Surface modification method for galvanized steel sheet and galvanized steel sheet surface modified accordingly

JP7640671B2Active Publication Date: 2025-03-05POHANG IRON & STEEL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023507729
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-08
Filing Date
2021-08-24
Publication Date
2025-03-05
Estimated Expiration
2041-08-24

AI Technical Summary

Benefits of technology

【0018】 本発明の一側面によると、表面改質処理を介して接着剤との接着力が効果的に向上したマグネシウム含有亜鉛めっき鋼板を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640671000002
    Figure 0007640671000002
  • Figure 0007640671000003
    Figure 0007640671000003
  • Figure 0007640671000004
    Figure 0007640671000004
Patent Text Reader

Abstract

A galvanized steel sheet according to one aspect of the present invention includes a base steel sheet; and a Zn-Al-Mg-based plating layer provided on at least one surface of the base steel sheet, wherein the Zn-Al-Mg-based plating layer includes a surface-modified region where cerium (Ce) is concentrated on a surface side of the Zn-Al-Mg-based plating layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a plated steel sheet for automobiles, and more particularly to a magnesium-containing zinc-plated steel sheet having effectively improved adhesive strength to a sealer adhesive. [Background technology]

[0002] Galvanized steel sheets, which are made by plating the surface of carbon-containing steel sheets with zinc or zinc alloy, are used as interior and exterior plate materials for automobiles. In particular, galvanized steel sheets or zinc alloy-plated steel sheets that contain magnesium (Mg) as a component of the plating layer to improve corrosion resistance have been commercialized and are widely used.

[0003] Generally, after processes such as molding, welding, and assembly, galvanized steel sheets for automobiles undergo a process of filling gaps between the inner and outer panels with an epoxy-based sealant adhesive to reduce noise from the automobile body. The epoxy-based sealant adhesive expands at approximately 200℃ or more during the curing process after painting, becoming porous. At this time, the epoxy-based sealant adhesive adheres closely to the galvanized steel sheet, effectively reducing noise and vibration from the automobile body.

[0004] It is known that there is no particular problem with the adhesive strength between an epoxy-based sealer adhesive and a plated steel sheet in a normal zinc-plated steel sheet or zinc alloy-plated steel sheet. However, in a zinc alloy-plated steel sheet containing magnesium (Mg) as a component of the plating layer, there is a problem that the adhesive strength between the sealer adhesive and the plated steel sheet is deteriorated by magnesium oxide formed on the surface of the plating layer. To solve this problem, a method of increasing the contact area by imparting roughness to the surface of the plating layer, or a method of increasing the chemical bonding strength of the interface by activating and modifying the outermost surface of the plating layer have been proposed, but these methods are not evaluated as practical methods for improving the adhesive strength between a magnesium (Mg)-containing zinc alloy plating layer and an epoxy-based sealer adhesive. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Korean Patent Publication No. 10-2018-0073855 (Published on July 3, 2018) Summary of the Invention [Problem to be solved by the invention]

[0006] According to one aspect of the present invention, there is provided a method for modifying the surface of a zinc-coated steel sheet to improve the adhesive strength between the magnesium-containing zinc-coated steel sheet and an adhesive, and a magnesium-containing zinc-coated steel sheet surface-modified accordingly.

[0007] The object of the present invention is not limited to the above-mentioned contents, and a person skilled in the art will have no difficulty in understanding further object of the present invention from the overall contents of this specification. [Means for solving the problem]

[0008] A galvanized steel sheet according to one aspect of the present invention includes a base steel sheet; and a Zn-Al-Mg-based plating layer provided on at least one surface of the base steel sheet, the Zn-Al-Mg-based plating layer including a surface-modified region where cerium (Ce) is concentrated on a surface side of the Zn-Al-Mg-based plating layer.

[0009] The surface modified region may include a convex portion provided by zinc-cerium nitrate salt (Zn-Ce-NO3-H2O) attached to the surface of the Zn-Al-Mg-based plating layer; and a concave portion provided by removing magnesium (Mg) from the surface of the Zn-Al-Mg-based plating layer.

[0010] The amount of the zinc-cerium nitrate salt (Zn-Ce-NO3-H2O) attached is 0.01 to 2.5 g / m 2 It can be.

[0011] The surface roughness of the surface modified region may be 1.2 to 1.6 μm based on the center line average roughness (Ra).

[0012] The Zn-Al-Mg-based plating layer may contain, by weight, 0.1 to 16% magnesium (Mg), 0.1 to 12% aluminum (Al), 0.0005 to 1.5% cerium (Ce), the remainder zinc (Zn), and unavoidable impurities.

[0013] A surface modification method for a galvanized steel sheet according to another aspect of the present invention includes the steps of: preparing a galvanized steel sheet having a Zn-Al-Mg-based plating layer formed on at least one surface of a base steel sheet; preparing an aqueous cerium nitrate solution; immersing the galvanized steel sheet in the aqueous cerium nitrate solution; and rinsing and drying the galvanized steel sheet immersed in the aqueous cerium nitrate solution.

[0014] The step of preparing the galvanized steel sheet includes the steps of preparing a Zn-Al-Mg-based coating bath; and immersing the base steel sheet in the Zn-Al-Mg-based coating bath to form a coating layer, and in the step of preparing the Zn-Al-Mg-based coating bath, a coating bath containing, by weight, 0.1 to 16% magnesium (Mg), 0.1 to 12% aluminum (Al), the remainder zinc (Zn), and unavoidable impurities is prepared, and the content of cerium (Ce) inevitably added to the coating bath can be suppressed to 0.01% or less (including 0%).

[0015] In the step of preparing the cerium nitrate aqueous solution, 15 to 25 g of cerium nitrate is dissolved in 1000 ml of water (H20), and then titrated with nitric acid (HNO3) to prepare a cerium nitrate aqueous solution having a pH of 3.2 to 3.8.

[0016] In the step of immersing in the cerium nitrate aqueous solution, the temperature of the cerium nitrate aqueous solution may be 20 to 80° C., and the immersion time of the galvanized steel sheet may be 10 to 150 seconds.

[0017] The above solutions to the problems described above are not intended to be exhaustive, and the various features of the present invention and their associated advantages and effects can be understood in more detail with reference to the following specific examples. Effect of the Invention

[0018] According to one aspect of the present invention, it is possible to provide a magnesium-containing zinc-plated steel sheet in which the adhesive strength with an adhesive is effectively improved through a surface modification treatment.

[0019] According to another aspect of the present invention, there is provided a method for modifying the surface of a zinc-plated steel sheet, which can effectively improve the adhesive strength between a magnesium-containing zinc-plated steel sheet and an adhesive.

[0020] The effects of the present invention are not limited to the above-mentioned matters, but can be interpreted as including technical effects that a person of ordinary skill in the art can infer from the matters described below. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a schematic diagram illustrating the concept of the surface modification treatment of the present invention, in which (a) is a schematic diagram illustrating a cross-section of a plating layer before the surface modification treatment, and (b) is a schematic diagram illustrating a cross-section of a plating layer after the surface modification treatment. [Diagram 2] 1(a) and (b) are schematic diagrams illustrating the concepts of cohesive failure and interfacial failure, respectively. [Diagram 3] (a) and (b) are photographs of the adhesive surface with cohesive failure and the adhesive surface with interfacial failure, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention relates to a method for surface modification of a galvanized steel sheet and a galvanized steel sheet surface-modified thereby, and preferred embodiments of the present invention will be described below. The embodiments of the present invention may be modified in various ways, and the scope of the present invention should not be construed as being limited to the embodiments described below. The embodiments are provided to further explain the present invention in detail to those skilled in the art to which the present invention pertains.

[0023] Hereinafter, a galvanized steel sheet according to an embodiment of the present invention will be described in more detail.

[0024] The galvanized steel sheet of the present invention may include a base steel sheet; and a Zn-Al-Mg-based plating layer provided on at least one surface of the base steel sheet.

[0025] The base steel sheet is not particularly limited, and can be interpreted as a concept including all steel sheets that can be generally applied to the manufacture of galvanized steel sheets. As an example, the base steel sheet of the present invention can be interpreted as a concept including not only cold-rolled steel sheets, hot-rolled steel sheets, and heat-treated steel sheets, but also wire rods and steel wires. In addition, the base steel sheet of the present invention is not particularly limited with respect to alloy composition, microstructure, etc. Preferably, the base steel sheet of the present invention may be a low-carbon cold-rolled steel sheet having a carbon (C) content of 0.05 wt% or less, but is not necessarily limited thereto.

[0026] The plating layer of the present invention will be described in more detail below. Unless otherwise specified, % in the alloy composition of the plating layer means % by weight.

[0027] The plating layer of the present invention is not particularly limited in its formation method. For example, the plating layer of the present invention can be formed by a hot-dip plating method, an electroplating method, a vacuum deposition plating method, etc., and can also be formed by a plating layer formation method involving an alloying treatment. Preferably, the plating layer of the present invention can be a zinc-based hot-dip plating layer, and more preferably, the plating layer of the present invention can be a Zn-Al-Mg-based hot-dip plating layer.

[0028] The plating layer of the present invention may be a Zn-Al-Mg-based plating layer containing, by weight, 0.1-16% magnesium (Mg), 0.1-12% aluminum (Al), the remaining zinc (Zn), and inevitable impurities. The plating layer of the present invention may further contain 0.0005-1.5% by weight of cerium (Ce) as a component that is not artificially added to the plating bath but is introduced into the plating layer via a surface modification treatment.

[0029] Magnesium (Mg), aluminum (Al), and zinc (Zn) undergo a ternary process reaction in the coating bath to form a liquid molten aluminum-magnesium alloy with a uniform composition. The surface of a steel strip that has passed through such a ternary coating bath is coated with liquid zinc-aluminum-magnesium. The liquid zinc-aluminum-magnesium can be formed into a Zn single-phase structure containing 1-4% aluminum (Al), a Mg single-phase structure containing 1-2% zinc (Zn), a MgZn2 single-phase structure, a Zn-MgZn2 binary structure, a Zn-Al binary structure, and a MgZn2-Zn-Al ternary structure while being cooled in the air. Such intermetallic compounds (single-phase structure, binary structure, ternary structure) can be formed in combination of two or more types in the coating layer depending on the composition range of the components in the coating bath, the coating bath temperature, and the cooling rate.

[0030] When exposed to the atmosphere, magnesium (Mg) in the coating layer reacts before zinc (Zn) to form magnesium hydroxide, and therefore plays a role in effectively improving the corrosion resistance of the coated steel sheet. In particular, magnesium (Mg) exists mainly as a MgZn2 single-phase structure, but can also exist in a binary process structure or a ternary process structure, or as a Mg single-phase structure containing 1 to 2% zinc (Zn). The surface layer side of the coating layer mainly has a MgZn2 single-phase structure in the form of a layer, which can more effectively improve the corrosion resistance of the coated steel sheet. Therefore, the Zn-Al-Mg-based coating layer of the present invention can contain 0.1% by weight or more of magnesium (Mg). It can preferably contain 0.5% by weight or more of magnesium (Mg), and more preferably contain 1.0% by weight or more of magnesium (Mg).

[0031] However, if the magnesium (Mg) content is excessive, not only will the effect of improving corrosion resistance be saturated, but magnesium (Mg) oxide-related dross may be formed in the plating bath, which may deteriorate plating properties, and even if a surface modification treatment is performed, an excessive amount of magnesium hydroxide may be formed in the surface layer of the plating layer, which may deteriorate the adhesive strength with an epoxy-based sealant adhesive. In addition, Zn-Al-Mg-based intermetallic compounds with high hardness may be excessively formed as the microstructure of the plating layer, which may deteriorate bending workability. Therefore, the Zn-Al-Mg-based plating layer of the present invention may contain 16% by weight or less of magnesium (Mg). It may preferably contain 12% by weight or less of magnesium (Mg), and more preferably contain 8% by weight or less of magnesium (Mg).

[0032] Aluminum (Al) reacts with zinc (Zn) and magnesium (Mg) in the coating bath to facilitate alloying, and the intermetallic compound containing aluminum (Al) formed during the solidification process acts as a corrosion barrier and can effectively contribute to improving corrosion resistance. Aluminum (Al) also suppresses the formation of magnesium (Mg)-based oxide dross and forms a sufficient amount of Zn-Al-Mg-based intermetallic compounds in the coating layer, so that it can effectively contribute to improving the corrosion resistance of the coated steel sheet. Therefore, the Zn-Al-Mg-based coating layer of the present invention can contain 0.1% by weight or more of aluminum (Al). It can preferably contain 0.5% by weight or more of aluminum (Al), and more preferably contain 1.0% by weight or more of aluminum (Al). However, if the content of aluminum (Al) is excessive, not only the effect of improving corrosion resistance is saturated, but also the coating bath temperature needs to be increased, and the vapor gas of magnesium (Mg) and zinc (Zn) generated at this time can have an adverse effect on the durability of the coating equipment. Furthermore, the Zn-Al-Mg intermetallic compounds having high hardness are excessively formed as the microstructure of the plating layer, which may deteriorate the bending workability. Therefore, the Zn-Al-Mg plating layer of the present invention may contain 12% by weight or less of aluminum (Al). It may preferably contain 9% by weight or less of aluminum (Al), and more preferably contain 6% by weight or less of aluminum (Al).

[0033] The Zn-Al-Mg-based coating layer of the present invention may contain the remaining zinc (Zn) and inevitable impurities in addition to the above-mentioned magnesium (Mg) and aluminum (Al). Here, the inevitable impurities may mean components that inevitably flow in during the manufacturing process of the coated steel sheet or components that flow in from the base steel sheet, and even if there is no specific limitation on the components that inevitably flow in, those of ordinary skill in the art can easily understand these components.

[0034] The Zn-Al-Mg-based plating layer of the present invention may further contain 0.0005 to 1.5% by weight of cerium (Ce). The cerium (Ce) contained in the Zn-Al-Mg-based plating layer of the present invention is not an artificially added component in the plating bath composition, but may flow into the Zn-Al-Mg-based plating layer as a component due to a surface modification treatment performed after the formation of the plating layer. In order to ensure the desired sealer adhesion, the content of cerium (Ce) flowing into the Zn-Al-Mg-based plating layer of the present invention may be limited to 0.0005% by weight or more. Preferably, the amount of cerium (Ce) flowing in may be limited to 0.001% by weight or more, and more preferably, the amount of cerium (Ce) flowing in may be limited to 0.005% by weight or more. However, if the content of cerium (Ce) flowing into the Zn-Al-Mg-based plating layer is excessive, the effect of improving the sealer adhesion is saturated, while cerium (Ce) precipitates at the grain boundaries of the Zn-Al-Mg-based intermetallic compound, which may deteriorate mechanical properties such as impact resistance and abrasion resistance. Therefore, the present invention can limit the content of cerium (Ce) flowing into the Zn-Al-Mg-based plating layer to 1.5 wt% or less. Preferably, the amount of cerium (Ce) flowing into the Zn-Al-Mg-based plating layer can be limited to 1.2 wt% or less, and more preferably, the amount of cerium (Ce) flowing into the Zn-Al-Mg-based plating layer can be limited to 1.0 wt% or less.

[0035] The Zn-Al-Mg-based plating layer of the present invention may have a microstructure contained in a normal Zn-Al-Mg-based plating layer. As an example, the Zn-Al-Mg-based plating layer of the present invention may contain, as a microstructure, one or more selected from the group consisting of a Zn single-phase structure containing 1-4% aluminum (Al), a Mg single-phase structure containing 1-2% zinc (Zn), a MgZn2 single-phase structure, a Zn-MgZn2 binary process structure, a Zn-Al binary process structure, and a MgZn2-Zn-Al ternary process structure, as well as other structures that inevitably flow in during the manufacturing process.

[0036] The surface layer of the Zn-Al-Mg-based plating layer of the present invention may include a surface-modified region introduced through a surface modification treatment, and the surface-modified region may have a greater concentration of cerium (Ce) than the central portion of the Zn-Al-Mg-based plating layer. As described below, the present invention uses a cerium nitrate aqueous solution to perform the surface modification treatment of the plating layer, so that zinc-cerium nitrate salt (Zn-Ce-NO3-H2O) can adhere to the surface of the plating layer. Therefore, a surface-modified region in which a certain amount or more of cerium (Ce) is concentrated on the surface can be formed.

[0037] Fig. 1 is a schematic diagram showing the concept of the surface modification treatment of the present invention, where (a) shows a cross section of a plating layer before the surface modification treatment, and (b) shows a cross section of a plating layer after the surface modification treatment. In Fig. 1(b), the shapes of the concave and convex parts are somewhat exaggerated in order to explain the concept of the surface modification treatment of the present invention, but it should be noted that the shapes of the concave and convex parts of the present invention are not necessarily limited to the shapes shown in Fig. 1(b).

[0038] As shown in Fig. 1(a), a Zn-Al-Mg-based coating layer 10 formed on a base steel sheet 1 contains a mixture of a Zn single-phase structure 11, a Zn-Mg-Al-based intermetallic compound 12, and a MgZn2 single-phase structure 13, of which the MgZn2 single-phase structure 13, which contains a large amount of oxidizable magnesium (Mg), is distributed mainly on the surface layer side of the coating layer 10. The magnesium (Mg) component of the MgZn2 single-phase structure 13 distributed on the surface layer of the Zn-Al-Mg-based coating layer 10 reacts with moisture (H2O) in the air to preferentially form magnesium hydroxide, which may act as a factor reducing the adhesion between the coating layer 10 and an epoxy sealer.

[0039] As shown in FIG. 1(b), the surface of the Zn-Al-Mg-based plating layer 10, which has been subjected to a surface modification treatment using a cerium nitrate aqueous solution, can be provided with a surface-modified region 20 having an uneven surface. Magnesium (Mg) on ​​the surface side of the plating layer 10 reacts with nitric acid in the cerium nitrate aqueous solution and dissolves into the aqueous solution, so that a corresponding region can be formed as a recess 21. Meanwhile, zinc (Zn) on the surface side of the plating layer 10 reacts with cerium (Ce) in the cerium nitrate aqueous solution to form zinc-cerium nitrate salt (Zn-Ce-NO3-H2O), so that a region to which the zinc-cerium nitrate salt (Zn-Ce-NO3-H2O) is attached can be formed as a protrusion 22. That is, the surface of the Zn-Al-Mg-based plating layer 10, which has been subjected to a surface modification treatment, can be provided with a surface-modified region 20 having an uneven surface, so that the physical contact area can be increased when bonding with an epoxy-based sealer adhesive. In addition, zinc-cerium nitrate salt (Zn-Ce-NO3-H2O) increases the chemical bonding strength when bonded to an epoxy-based sealant adhesive, thereby more effectively improving the adhesive strength between the plating layer 10 and the epoxy-based sealant adhesive.

[0040] The amount of zinc-cerium nitrate salt (Zn-Ce-NO3-H2O) attached is 0.01 to 2.5 g / m 2 This corresponds to a coating weight of zinc-cerium nitrate salt (Zn-Ce-NO3-H2O) of 0.01 g / m 2 If the level is less than this, the desired effect of improving adhesive strength cannot be fully expected. A more preferable adhesion level of zinc-cerium nitrate salt (Zn-Ce-NO3-H2O) is 0.1 g / m 2In addition, as the amount of zinc-cerium nitrate salt (Zn-Ce-NO3-H2O) attached increases, the adhesive strength with the epoxy-based sealant adhesive tends to increase, but above a certain level, the effect becomes saturated and it may cause painting defects such as blisters and pinholes in the subsequent painting process. Therefore, the amount of zinc-cerium nitrate salt (Zn-Ce-NO3-H2O) attached is set to 2.5 g / m 2 It can be managed at the following levels:

[0041] The surface roughness of the surface-modified region can be in the range of 1.2 to 1.6 μm based on the center line average roughness (Ra). If the surface roughness of the surface-modified region does not reach a certain level, it means that the uneven shape of the surface of the surface-modified region is not formed to the desired level, so the present invention can limit the surface roughness of the surface-modified region to 1.2 μm or more based on the center line average roughness (Ra). If the surface roughness of the surface-modified region exceeds a certain level, the adhesive strength may deteriorate as the effective contact area becomes smaller, so the present invention can limit the surface roughness of the surface-modified region to a range of 1.6 μm or less based on the center line average roughness (Ra).

[0042] Hereinafter, a method for modifying the surface of a galvanized steel sheet according to another embodiment of the present invention will be described in more detail.

[0043] The surface modification method of the galvanized steel sheet of the present invention includes the steps of: preparing a galvanized steel sheet having a Zn-Al-Mg-based plating layer formed on at least one surface of a base steel sheet; preparing an aqueous cerium nitrate solution; immersing the galvanized steel sheet in the aqueous cerium nitrate solution; and rinsing and drying the galvanized steel sheet immersed in the aqueous cerium nitrate solution.

[0044] The step of preparing the galvanized steel sheet includes the steps of preparing a Zn-Al-Mg-based coating bath; and immersing the base steel sheet in the Zn-Al-Mg-based coating bath to form a coating layer, and in the step of preparing the Zn-Al-Mg-based coating bath, a coating bath containing, by weight, 0.1 to 16% magnesium (Mg), 0.1 to 12% aluminum (Al), the remainder zinc (Zn) and unavoidable impurities is prepared, and the content of cerium (Ce) inevitably added to the coating bath can be suppressed to 0.01% or less (including 0%).

[0045] The base steel sheet provided in the surface modification method of the present invention corresponds to the base steel sheet of the above-mentioned plated steel sheet, and therefore the description of the base steel sheet provided in the surface modification method is substituted for the description of the base steel sheet of the above-mentioned plated steel sheet. In addition, the Zn-Al-Mg-based plating bath composition provided in the surface modification method of the present invention corresponds to the plating layer composition of the above-mentioned plated steel sheet, except for the point that cerium (Ce) is not artificially added, and therefore the description of the Zn-Al-Mg-based plating bath composition provided in the surface modification method is substituted for the description of the plating layer composition of the above-mentioned plated steel sheet. In addition, since the plating conditions such as the plating bath temperature and the base steel sheet temperature during immersion in the plating bath are normal Zn-Al-Mg plating conditions, even without any special description therefor, a person of ordinary skill in the art can prepare the Zn-Al-Mg-based plating bath of the present invention and form a desired plating layer without adding any special technical means.

[0046] In the step of preparing the cerium nitrate aqueous solution, 15 to 25 g of cerium nitrate is dissolved in 1000 ml of water (H20), and then titrated with nitric acid (HNO3) to prepare a cerium nitrate aqueous solution having a pH of 3.2 to 3.8. For a desired level of reactivity of the surface modification, the amount of cerium nitrate dissolved in 1000 ml of water (H20) may be 15 g or more. However, if the amount of cerium nitrate dissolved is excessive, sludge may be generated, so the amount of cerium nitrate dissolved in 1000 ml of water (H20) may be limited to 25 g or less. If the pH of the cerium nitrate aqueous solution is too low, etching of the plating layer may proceed faster than the formation of a cerium (Ce)-based coating layer, and the surface modification may proceed slowly, so the pH of the cerium nitrate aqueous solution may be limited to 3.2 or more. However, if the pH of the cerium nitrate aqueous solution is excessively high, the etching rate and surface modification rate of the plating layer will be slow, so the pH of the cerium nitrate aqueous solution can be limited to 3.8 or less.

[0047] In the step of immersing in the cerium nitrate aqueous solution, the temperature of the cerium nitrate aqueous solution may be 20 to 80° C., and the immersion time of the galvanized steel sheet may be 10 to 150 seconds. If the temperature of the cerium nitrate aqueous solution is too low or the immersion time of the galvanized steel sheet is too short, the surface modification at a desired level is not achieved, so the temperature of the cerium nitrate aqueous solution may be limited to 20° C. or more, and the immersion time of the galvanized steel sheet may be limited to 10 seconds or more. If the temperature of the cerium nitrate aqueous solution is too high or the immersion time of the galvanized steel sheet is too long, fumes may be generated, making the work difficult, so the temperature of the cerium nitrate aqueous solution may be limited to 80° C. or less, and the immersion time of the galvanized steel sheet may be limited to 150 seconds or less.

[0048] A magnesium-containing zinc-plated steel sheet that has been subjected to a surface modification treatment using the surface modification method of the present invention can effectively improve the adhesive strength with an epoxy-based sealant adhesive while maintaining the effect of improving corrosion resistance due to the addition of magnesium. EXAMPLES

[0049] The present invention will be described in more detail with reference to the following examples. However, it should be noted that the following examples are merely intended to more specifically explain the present invention and are not intended to limit the scope of the present invention to the following examples.

[0050] (Example) Low-carbon steel with a carbon content of 0.05% by weight or less was cut into 75 x 150 mm (0.8 mm thick), degreased with acetone, and then immersed in a hot-dip Zn-Al-Mg plating bath to prepare Zn-Al-Mg alloy-plated steel sheets (plating layer thickness: 20 μm) as test pieces. Two test pieces were prepared under the same conditions to form a pair, and the composition of the hot-dip Zn-Al-Mg plating bath was as shown in Table 1.

[0051] 20g of cerium nitrate powder was dissolved in 1000ml of water (H2O), and then titrated with nitric acid (HNO3) to prepare a cerium nitrate aqueous solution with a pH of 3.5. Then, each test piece was immersed in the prepared cerium nitrate aqueous solution, washed with water and dried to carry out a surface modification treatment. At this time, the temperature of the cerium nitrate aqueous solution was maintained at 50°C, and the immersion time of each test piece was the same as the conditions in Table 1.

[0052] After the surface modification treatment, the sealer adhesive strength of each test piece was evaluated. For each pair of test pieces, an epoxy-based sealer adhesive (Sunrise's 766MD) was applied to an area of ​​15 x 15 mm and bonded, and then foamed and cured at a temperature of 200 ° C for 2 minutes. A shear stress of 20 MPa was applied to the pair of foamed and cured bonded test pieces in a direction parallel to the sealer adhesive surface to separate them into individual test pieces, and the separated adhesive surfaces were observed to evaluate the sealer adhesive strength. Figure 2 (a) and (b) are schematic diagrams showing the concepts of cohesive failure and interfacial failure, respectively. At this time, the sealer adhesive strength was evaluated based on the area ratio of the epoxy-based sealer adhesive remaining on the adhesive surfaces of both test pieces. That is, when the area of ​​all the adhesive surfaces of the separated test pieces where the epoxy-based sealer adhesive was applied was 95% or more, it was evaluated as cohesive failure (very good, ◎), when the area of ​​any one adhesive surface of the separated test pieces where the epoxy-based sealer adhesive was applied was 80% or more, it was evaluated as semi-cohesive failure (good, ○), and when the area of ​​any one adhesive surface of the separated test pieces where the epoxy-based sealer adhesive was applied was less than 80%, it was evaluated as interfacial failure (insufficient, ×). The area ratio of the epoxy-based sealer adhesive listed in Table 1 below means the applied area of ​​the epoxy-based sealer adhesive observed on the adhesive surface of each test piece separated from the bond of a pair of test pieces. Figures 3(a) and (b) are photographs of the adhesive surface of the cohesive failure and the adhesive surface of the interfacial failure, respectively. In Figures 3(a) and (b), the relatively darkest areas are the areas where the epoxy-based sealer adhesive was applied, and the grayish white areas are the base steel plate areas.

[0053] [Table 1]

[0054] As shown in Table 1, test pieces No. 4 to No. 11, which satisfy the conditions of the surface modification of the present invention, have excellent or very excellent sealer adhesion, whereas test pieces No. 2 and No. 3, which do not satisfy the conditions of the surface modification of the present invention, have insufficient sealer adhesion.

[0055] Although the present invention has been described in detail with reference to the embodiments, other embodiments may be possible, and therefore the spirit and scope of the claims set forth below should not be limited to the embodiments. [Explanation of symbols]

[0056] 1 Base steel sheet 10 Plating layer 11 Zn single phase structure 12 Zn-Mg-Al intermetallic compounds 13 MgZn2 single phase structure 20 Surface Modification Area 21 Recess 22 Convex

Claims

1. Base steel sheet; and A Zn-Al-Mg-based plating layer is provided on at least one surface of the base steel sheet, The Zn-Al-Mg-based plating layer includes a surface-modified region where cerium (Ce) is concentrated on the surface side of the Zn-Al-Mg-based plating layer, and the surface-modified region has a coating weight of 0.01 to 2.5 g / m 2 Zinc-cerium nitrate salt (Zn-Ce-NO 3 -H 2 O), and the surface roughness of the surface modified region is 1.2 to 1.6 μm based on the center line average roughness (Ra).

2. The surface modified region is The zinc-cerium nitrate salt (Zn-Ce-NO) attached to the surface of the Zn-Al-Mg-based plating layer 3 -H 2 O) a protrusion provided by; and 2. The galvanized steel sheet according to claim 1, comprising a recess provided by removing magnesium (Mg) from a surface layer of the Zn-Al-Mg-based plating layer.

3. 2. The galvanized steel sheet according to claim 1, wherein the Zn-Al-Mg based plating layer contains, by weight %, 0.1 to 16% magnesium (Mg), 0.1 to 12% aluminum (Al), 0.0005 to 1.5% cerium (Ce), the remainder zinc (Zn), and inevitable impurities.

4. A step of preparing a zinc-plated steel sheet having a Zn-Al-Mg-based plating layer formed on at least one surface of a base steel sheet; Water (H20) 1000 Dissolving 15-25 g of cerium nitrate per ml, and then titrating with nitric acid (HNO 3 ) to prepare an aqueous cerium nitrate solution with a pH of 3.2-3.8; immersing the galvanized steel sheet in the cerium nitrate aqueous solution; and The method for modifying the surface of a galvanized steel sheet includes the steps of rinsing the galvanized steel sheet immersed in the cerium nitrate aqueous solution and drying the galvanized steel sheet.

5. The step of preparing the galvanized steel sheet includes: Providing a Zn-Al-Mg based plating bath; and The method includes the step of immersing the base steel sheet in the Zn-Al-Mg-based coating bath to form a coating layer, In the step of preparing the Zn-Al-Mg-based plating bath, 5. The surface modification method of claim 4, wherein a plating bath containing, by weight, 0.1 to 16% magnesium (Mg), 0.1 to 12% aluminum (Al), the remainder zinc (Zn), and inevitable impurities is prepared, and the content of cerium (Ce) inevitably added to the plating bath is suppressed to 0.01% or less (including 0%).

6. In the step of immersing in the cerium nitrate aqueous solution, The temperature of the cerium nitrate aqueous solution is 20 to 80° C. The method for modifying a surface of a galvanized steel sheet according to claim 4, wherein the immersion time of the galvanized steel sheet is 10 to 150 seconds.

Citation Information

Patent Citations

  • Conversion coating layer, method for forming same and solution

    JP1998501303A

  • Surface treatment film for galvanized steel sheet and surface treated steel sheet

    JP2001158973A

  • Hot dip zn-al-mg alloy plated steel sheet and production method therefor

    JP2002241962A

  • Surface treatment method for substrates coated with a protective layer

    JP2014501854A

  • A Cerium Composition for Forming Film, A Method for Preparing Cerium, Silicate and Silane Film Having Superior Anti-Corrosion By Using the Same and Steel Sheet Prepared Thereby

    KR100742844B1